Kegel exercises and perineal wound healing among postpartum mothers: A qualitative study - Yunitasari, Eva; Saragih, Septina Boru; Nursanti, Indah; Yetiani, Novin (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Perineal wounds following childbirth are common, particularly among women who experience vaginal or perineal tears. When healing is delayed, these wounds may lead to serious postpartum complications, including infection, bleeding, and increased maternal morbidity. Kegel exercises are widely recognized as a simple, non-pharmacological intervention that strengthens pelvic floor muscles and may support the healing process of perineal wounds. However, limited attention has been given to postpartum mothers’ personal experiences in performing these exercises during the recovery period. Purpose: To explore postpartum mothers’ experiences in practicing Kegel exercises as part of perineal wound healing at the Gadingrejo Community Health Center. Method: A qualitative study with a phenomenological approach was employed to capture mothers’ lived experiences. Participants were selected through purposive sampling, involving eight postpartum mothers who met the inclusion criteria. Data were collected through in-depth interviews and direct observation. Thematic analysis was conducted to identify recurring patterns and meanings related to the implementation of Kegel exercises. Results: The findings revealed five main themes: (1) timing of Kegel exercise initiation, (2) initial physical complaints after childbirth, (3) perceived benefits of the exercises, (4) vaginal care practices, and (5) dietary patterns during the postpartum period. Observations of wound healing using the REEDA assessment showed a gradual improvement from day one to day seven. Initially, most participants demonstrated poor wound healing characteristics, which progressed to good wound healing by the end of the observation period. Conclusion: Postpartum mothers who practiced Kegel exercises experienced better perineal wound healing compared to their initial condition. These findings suggest that Kegel exercises may contribute to accelerating the perineal wound healing process. In addition, proper vaginal care and adequate nutritional intake appear to play supportive roles in promoting recovery among postpartum women.